The Influence of Workload and Work Facilities on the Performance of the Firefighting and Rescue Field of BPBD Karawang - Silviyana, Hera; Budi Rismayadi; Wike Pertiwi; Norliana Sarpin (Research in Management of Technology and Business, 2024)
This research aims to determine and analyze the influence of work load and work facilities on the performance of the Karawang BPBD Fire and Rescue Sector, both variable and simultaneous. This research uses a quantitative approach, because the data used in this research is expressed in the form of numbers. The technique used in collecting the data is using a questionnaire in the form of a number of questions given to respondents to be filled in according to the actual situation. The research design used in this research is verification research with quantitative data analysis and data collection using a closed questionnaire. Based on data analysis, it appears that workload and work facilities have a positive and significant influence on employee performance and there is a close relationship between workload and work facilities and employee performance. And it was found that the higher the workload experienced by employees, the more significant the impact on their performance. Apart from that, good work facilities can improve employee performance positively. The research results show that workload conditions and work facilities can simultaneously contribute to employee performance levels.